Importância do prado de capim marinho (Halodule writhii Aschers) na composição da fauna de Crustacea Brachyura e na dinâmica trófica das espécies de Callinectes (Crustacea, Portunidae) na ilha de Itamaracá - Pernambuco - Brasil - Moura, Noely Fabiana Oliveira de (Universidade Federal de São Carlos, 2006)
With aim to know the community structure of the Crustacea Brachyura and analyze the trophic dynamics of the species Callinectes dane, C. larvatus e C. ornatus in the seagrass bed of Halodule wrightii Aschers, studies were carried out during a dry period (February, 2001 and September to December, 2001) and the wet period (March to August, 2001) in the Forno da Cal beach, Itamaraca Island, Pernambuco, Brazil. The sampling method adopted was nocturnal trawling on the seagrass using a small (2m width) bottom net with internal mesh of 5mm and external of 2mm. Additional samplings were carried out on a period of 24 hours, in February, May, July, September and December, 2001. Samplings were also carried out on the adjacent sandy flat without vegetation, in March, June, August and December, having as objective to compare the biomass, abundance and diversity of this habitat with the seagrass in this same period. To determinate the gastric evacuation rate in the Callinectes sp., experiment was carried out. The results indicate that the Portunidae family contributed with 93% of the total captures. The species Callinectes ornatus, C. danae, C. larvatus and Portunus ordwayi were the most frequent. The highest density occurred in March, positively correlating with the air temperature, and the highest biomass was observed in July, with a positive correlation to density of cast algae. The seagrass presented the highest averages of densities, biomass, number of species, richness and diversity when compared to the adjacent sandy flat. Even if the number of species observed in the sand is higher, these presented well-distributed in the environment, with equitability value higher than in the seagrass. Animal organic matter, Gastropoda and Macrophyta were the food items that most contributed in the analysis of the stomach content of the species C. danae, C. larvatus and C. ornatus. It was observed that the smallest organisms have fed of small preys and with low mobility, as in the case of highest consume of Polychaeta, Copepoda and Amphipoda by specimens of smaller carapace width. Two feeding rhythms were observed for Callinectes: a diurnal one from 4:00 to 9:00 am and a nocturnal one between 21:00 and 22:00 pm. The evacuation rate (E) obtained by the regression analysis was E = 33.26% VE h-1. The daily ration in the sampled months in the 24-hour analyses was of 798.24% SV (the stomach fullness). After transforming the stomach fullness to somatic weight a day, the observed value was 20.748%.d-1. Then, C. ornatus with weigh of 1 g may consume 0.207 g food/ day. The seagrass bed represented as an important food source to Brachyura s population, due to the diversity of preys and refuge area, not only by the vegetation of seagrass but also by the abundance of cast algae, especially for the species Callinectes danae, C. larvatus and C. ornatus.
Keywords: Caranguejo; Brachyura; Nutrição; Halodule wrightii; Brachyura; Callinectes; Halodule wrightii; Feeding; Daily ration; CIENCIAS BIOLOGICAS::ECOLOGIA